2005
DOI: 10.1099/ijs.0.63780-0
|View full text |Cite
|
Sign up to set email alerts
|

Desulfotomaculum carboxydivorans sp. nov., a novel sulfate-reducing bacterium capable of growth at 100 % CO

Abstract: A moderately thermophilic, anaerobic, chemolithoheterotrophic, sulfate-reducing bacterium, strain CO-1-SRB T , was isolated from sludge from an anaerobic bioreactor treating paper mill wastewater. Cells were Gram-positive, motile, spore-forming rods. The temperature range for growth was 30-68 6C, with an optimum at 55 6C. The NaCl concentration range for growth was 0-17 g l "1; there was no change in growth rate until the NaCl concentration reached 8 g l . The pH range for growth was 6?0-8?0, with an optimum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 35 publications
4
69
0
2
Order By: Relevance
“…A carboxydovore-related CODH with 94% nucleotide identity to Desulfotomaculum carboxydivorans CO-1-SRB was identified in the TT107 metagenome (Supplementary Table S6). D. carboxydivorans CO-1-SRB is a bacterium that was cultured in 100% pCO headspace and with the absence of any other electron donors, carbon substrates and sulfate (Parshina et al, 2005). Parshina et al (2005) found that the D. carboxydivorans CO-1-SRB oxidized CO to CO 2 while reducing H 2 O to H 2 and, upon the addition of sulfate, switched to sulfate reduction.…”
Section: Deep Subsurface Metabolism C Magnabosco Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…A carboxydovore-related CODH with 94% nucleotide identity to Desulfotomaculum carboxydivorans CO-1-SRB was identified in the TT107 metagenome (Supplementary Table S6). D. carboxydivorans CO-1-SRB is a bacterium that was cultured in 100% pCO headspace and with the absence of any other electron donors, carbon substrates and sulfate (Parshina et al, 2005). Parshina et al (2005) found that the D. carboxydivorans CO-1-SRB oxidized CO to CO 2 while reducing H 2 O to H 2 and, upon the addition of sulfate, switched to sulfate reduction.…”
Section: Deep Subsurface Metabolism C Magnabosco Et Almentioning
confidence: 99%
“…D. carboxydivorans CO-1-SRB is a bacterium that was cultured in 100% pCO headspace and with the absence of any other electron donors, carbon substrates and sulfate (Parshina et al, 2005). Parshina et al (2005) found that the D. carboxydivorans CO-1-SRB oxidized CO to CO 2 while reducing H 2 O to H 2 and, upon the addition of sulfate, switched to sulfate reduction. In TT107, Desulfotomaculum, is the most Figure 4 The normalized abundances of PEGs within the 'carbon monoxide induced hydrogenase' RAST category are shown.…”
Section: Deep Subsurface Metabolism C Magnabosco Et Almentioning
confidence: 99%
“…Tests for assessing selected physiological features of D. carboxydivorans (DSM 14880, VKM B-2319;Parshina et al 2005b) were all performed in serum bottles incubated in a temperature-controlled (55°C) shaker type RFI-125 (Infors AG, Basel, Switzerland) at 200 rpm. The basal medium contained (in mM): NaCl 5.1, NH 4 Cl 5.6, CaCl 2 ·2H 2 O 0.7, MgCl 2 ·6H 2 O 0.5, Na 2 S·9H 2 O 0.6, yeast extract 500 mg l −1 , and 1 ml l −1 of an acid-and-alkaline trace element solution according to Stams et al (1993).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…thermosynthrophicum were shown capable of CO utilization at CO levels in the gas phase up to 50 kPa (Parshina et al 2005a). The recently isolated Desulfotomaculum carboxydivorans is the first sulfate reducer that shows uninhibited growth on 180 kPa CO at 55°C, both in the presence and absence of sulfate (Parshina et al 2005b). In the absence of sulfate, it grows hydrogenogenically on CO producing nearly equimolar amounts of H 2 and CO 2 (Parshina et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…The previously described mesophilic (optimal temperature 25-40 u C) Desulfotomaculum species are D. ruminis (Campbell & Postgate, 1965), D. acetoxidans (Widdel & Pfennig, 1977), D. sapomandens (Cord-Ruwisch & Garcia, 1985), D. aeronauticum (Hagenauer et al, 1997), D. halophilum (Tardy-Jacquenod et al, 1998) and D. gibsoniae (Kuever et al, 1999). The thermophilic (optimal temperature 50-70 u C) species are D. alkaliphilum (Pikuta et al, 2000), D. australicum (Love et al, 1993), D. carboxydivorans (Parshina et al, 2005), D. geothermicum (Daumas et al, 1988), D. kuznetsovii (Nazina et al, 1989), D. luciae (Liu et al, 1997), D. nigrificans (Werkman & Weaver, 1927;Campbell & Postgate, 1965), D. putei (Liu et al, 1997), D. solfataricum (Goorissen et al, 2003), D. thermoacetoxidans (Min & Zinder, 1990), D. thermobenzoicum with two subspecies, namely subsp. thermobenzoicum and subsp.…”
mentioning
confidence: 99%